Mortality Risk Among a Sample of Sexual Minority Women: A Focus on The Role of Sexual Identity Disclosure - Everett, Bethany G. (Soc Sci Med, 2021)
Almost no research has examined factors that contribute to mortality risk among sexual minority women (SMW). This study capitalizes on a 21-year community-based longitudinal study of SMW to examine the association between sexual identity disclosure and mortality risk. Forty-nine SMW who were recruited in 2000–01 or 2010–12 (6.3% of the sample), were confirmed dead by 2019. The mean age at death was 56.5 years. We used Cox proportional hazard models to show that SMW who had disclosed their sexual identity to 100% of their immediate family members had a 70% reduction in the risk of mortality compared to SMW who disclosed to less than 33% of their immediate family, after adjusting for several sociodemographic and health variables. Our results suggest that facilitating acceptance of SMW and their ability to disclose their identity may be an important way to improve health and life expectancy among SMW.